La práctica del voleibol y su incidencia en la etapa de iniciacion en los alumnos varones de 11-12 años de la escuela Alonso de Mercadillo de la ciudad de Loja - Castillo Roa, Juan Pablo (2014)
This thesis entitled " VOLLEYBALL PRACTICE AND ITS IMPACT ON THE STAGE STUDENT START IN MALES 11-12 YEARS OF ALONSO DE MARKET SCHOOL CITY Loja " was performed in order to know Ignorance and impractical volleyball at the top of initiation into the male students 11-12 years of Market Alonso de Loja City school to implement corrective action to enable stakeholders to raise awareness and raise the level of effort for the improvement of this problematic. The objectives have been approved foster the overall objective to playing volleyball training future volleyball players of the sport , with clear criteria for personality , function and knowing the teaching-learning process is required and thus promote a better quality of play in male students 11-12 years of Alonso School Market City Loja. , thanks to the specific objectives was approved projected Teaching the fundamentals of volleyball through introductory games with a fun and educational approach to male students 11 -12 years of Alonso School City Market Shop , play Create a culture in which children should not wait to be adults to start playing or directing a play, discover talents with better prospects for future performance Achieving and have children with a capacity of optimal movement so you can function in life with health. The investigated population was established by population are athletes training in a number 2 Physical Education teachers and 30 students . Finally clear and relevant results are obtained of students claim that their teacher does not teach them the fundamentals of volleyball because they have not been taught the sport and do not like , of teachers do not motivate students this sport because they do not like the sport and find it very difficult to practice and of students believe that if they would join the sports organization volleyball because they like the sport and excel in it and students do not like to be part of the sport organization volleyball because they dislike the sport and do not know it.